PENGEMBANGAN SISTEM INFORMASI ABSENSI BERBASIS WEB MOBILE DALAM MENINGKATKAN KEDISIPLINAN DAN KARAKTER SISWA DI SMP NEGERI 1 PRINGSEWU - Asiyani, Lusi; Suyono, Suyono; Mazdayani, Mazdayani (YHMM PUBLISHING, 2025)
The development of information technology in education has encouraged schools to implement more effective and efficient administrative systems, including student attendance management. SMP Negeri 1 Pringsewu still uses a manual attendance system which has several weaknesses, such as delays in data processing, risk of data loss, and ineffective monitoring of student discipline. This study aims to develop a web mobile-based attendance information system to improve attendance management effectiveness and support the enhancement of student discipline and character building. The research method used was Research and Development (R&D) with data collection techniques including observation, interviews, and literature studies. System testing was conducted on 61 respondents consisting of 2 teachers, 1 administrative staff member, 3 homeroom teachers, and 55 students using a Likert scale questionnaire. The results showed that the system achieved a success rate of 87% categorized as very good. The usability aspect obtained 90%, data accuracy 88%, monitoring effectiveness 86%, improvement in student discipline 84%, and character strengthening 83%. The web mobile-based attendance system was considered capable of assisting schools in managing student attendance in real time while supporting the development of discipline and responsibility among students in a sustainable manner.